Kontribusi System Informasi Manajemen Terhadap Ketepatan Kebijakan Sekolah - Ilham Rafi (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
This study aims to analyze the contribution of Management Information Systems to the accuracy of school policies. The utilization of Management Information Systems is an important factor in supporting data-based and accurate decision-making processes. This research employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation involving school management, teachers, and administrative staff. The data were analyzed using data reduction, data display, and conclusion drawing techniques. The results indicate that Management Information Systems have a positive contribution to the accuracy of school policies, particularly in program planning, academic and administrative data management, and school performance evaluation processes. However, the effectiveness of system utilization is still influenced by human resource competencies and the level of data integration across school units. These findings emphasize the importance of optimizing Management Information Systems as a foundation for accurate and accountable school policy formulation.